Cabaret [compact disc] - Kander, John; Ebb, Fred; Isherwood, Christopher, 1904-1986; Haworth, Jill; Gilford, Jack; Convy, Bert; Lenya, Lotte; Grey, Joel, 1932-; Hastings, Hal, 1916-1973; Van Druten, John, 1901-1957 (Columbia, 1986)
Based on the play by John Van Druten and stories by Christopher Isherwood is a stunning musical with the original Broadway cast.